2014
DOI: 10.1186/s12888-014-0278-8
|View full text |Cite
|
Sign up to set email alerts
|

Major depressive disorder in Parkinson’s disease: a cross-sectional study from Sri Lanka

Abstract: BackgroundDepression is common in Parkinson’s disease (PD), and has a significant impact on the functional level of those affected. It is well studied in Western populations but data from Asia is limited. This study aims to estimate the prevalence of depression among PD patients attending a tertiary care outpatient clinic in Sri Lanka and identify potential risk factors.MethodsOne hundred and four consecutive idiopathic PD patients as defined by the United Kingdom Parkinson’s Disease Society Brain Bank Diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 31 publications
2
21
0
3
Order By: Relevance
“…The only community based study conducted in the Colombo District reported a lifetime depression prevalence of 6.6% rising to 11.2% if the functional impairment criterion was excluded [4]. Studies among clinical samples have reported high rates of depression of 27.9% among patients with chronic renal failure, and 37.9% among patients with Parkinson disease in Sri Lanka [6,7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The only community based study conducted in the Colombo District reported a lifetime depression prevalence of 6.6% rising to 11.2% if the functional impairment criterion was excluded [4]. Studies among clinical samples have reported high rates of depression of 27.9% among patients with chronic renal failure, and 37.9% among patients with Parkinson disease in Sri Lanka [6,7].…”
Section: Discussionmentioning
confidence: 99%
“…The likelihood of having depression in the presence of a chronic illness is significantly higher than in the absence of a chronic medical illness. High prevalence of depression have been reported in patients with Parkinson disease (37.5%), chronic renal failure (27.9%), and in elderly patients in a medical ward in Sri Lanka [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…), что затрудняет ее диаг-ностику [6]. У большинства пациентов выявляются легкие и уме-ренные депрессивные расстройства, гораздо реже -тяжелая депрессия [10,11]. По данным T. Ketharanathan и соавт.…”
Section: о б з о р ыunclassified
“…По данным T. Ketharanathan и соавт. [11], частота депрессии ассоциируется с семейным статусом (наиболее часто выявляется у разведенных), уровнем обра-зования (лица с высшим образованием реже страдают де-прессивными расстройствами), со стадией болезни по шка-ле Хен и Яра (выявляется у 8,3% пациентов с I-II стадиями, у 49,1% с III стадией, у 40% с IV-V стадиями). В нашем ис-следовании не отмечено статистически значимой корреля-ции между депрессией и возрастом начала болезни, продол-жительностью заболевания, суточной дозой противопар-кинсонических препаратов и гендерной принадлежностью.…”
Section: о б з о р ыunclassified
“…A study on outdoor patients presented to the same hospital showed the prevalence of depression as 22.4% (12) However, in this study, the rate of prevalence was lower in older age group (above 61 years) compared to their younger counterparts (aged below 30 years). Other studies have also reported high prevalence of depression in patients with chronic illnesses (13,14). Two community studies in Sri Lankan involving older adults report high prevalence of depression; one study which included predominantly a Sinhalese subjects has reported the prevalence rate of 27.8% (15) while the other study which included all three major ethnic groups reported the rate of 31.8% (16).…”
Section: Introductionmentioning
confidence: 97%